A case of amniotic band syndrome with bilateral epibulbar choristoma. Issue 11 (November 1992) - Murata, T; Hashimoto, S; Ishibashi, T; Inomata, H; Sueishi, K
Abstract : An autopsy case of amniotic band syndrome with bilateral epibulbar choristoma is described. The left eye reveals a complex choristoma and the right eye a dermis-like choristoma. Both choristomatous lesions included lenticular tissue suggesting that rupture of the amnion, which is the initial event of amniotic band syndrome, might have occurred at about the fourth week of gestation. Since the other systemic manifestations of amniotic band syndrome are considered to be compression deformities of the fetus caused by oligohydramnios or amniotic band, the occurrence of epibulbar choristomas in both eyes in this case suggests that a compression mechanism may play a role in the pathogenesis of epibulbar choristoma.